IKLIM KOMUNIKASI RRI PALANGKA RAYA SEBAGAI LEMBAGA PENYIARAN PUBLIK - Aquarini aquarini; Artini Suparmo; Deli Anhar (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2014)
A communications climate and organization represent matter which need to become attention a organizational head because the factor many at least follow to influence employees behaviour. Communications in any context is elementary form of adaptation to environment. To be able to create communications climate and good organization require to comprehend both the things and also situation of employees specially in environment work Radio Republic Of Indonesia office of Palangka Raya.Pursuant to breakdown of above can be raised by the following problem formula: How communications climate of RRI Palangka Raya as Institute Broadcasting Of Public. While this Research aim to to find picture how communications climate in RRI Palangka Raya as Institute Broadcasting of Public.Approach method which is used in this research is approach of quantitative deskriftif with analysis percentage of mean to see communications climate picture in RRI Palangka Raya as Institute Broadcasting. Conceptually communications climate of RRI Palangka Raya have individuality as institute broadcasting of public especially its employees attitude picture.As for result of analysis and solution of this thesis is Climate communications in RRI Palangka Raya can be described as an atmosphere having a meaning of to all employees in running its duty as employees of RRI after there is change of position as institute broadcasting of public (LPP). This indicate that after change as LPP, employees of RRI Palangka Raya also feel change, do not only serving public externally but also internally between employees. As employees of RRI Palangka Raya, they have binding according to organizational communications climate dimension to is to supporting each other in attainment of target service of public, involvement in so many duty and role of RRI Palangka Raya in running function of social mass media, beside factor each other trusting, to be accompanied by relation/link credibility and confidence and also openness in organization, which giving meaning at climate of komunikadi in RRI Palangka Raya.